Enhancing young people's individual skills and knowledge. The case of vulnerable youth participating in co-creative policymaking in housing in the city of Barakaldo - Lorenz, Usue (Frontiers in Sustainable Cities, 2023)
This research aims to explore in what extent young people can enhance their individual skills, knowledge, attitudes, and behaviors by taking part in urban policymaking co-creation processes. The empirical study conducted within the UPLIFT project is based on two main theoretical influences: co-creation and youth participation in policymaking and the capability approach. The author found that the young participants in the UPLIFT co-creation process in Barakaldo who were encountering vulnerabilities or difficulties in housing, experienced positive individual effects from their participation in the process. Framed in terms of the Capability Approach, the process impacts positively on young people’s individual abilities (individual factors) that may influence their opportunities (capabilities) and life strategies (functionings) in the housing domain. In the following lines, I also suggest a set of critical aspects that need to be pursued in a co-creative policymaking process to help increase the vulnerable young participants’ knowledge and attitudes towards community planning initiatives in the field of urban policymaking.